Cicero and Political Trees - van der Blom, Henriette (Ciceroniana On Line, 2023)
Cicero used and represented trees for a variety of purposes, but this article focuses on Cicero’s attitudes to political usage of trees within a wider context of “botanising rulers”, triumphing trees, Roman euergetism and spectacle, and sacred trees. Starting with trees within a Roman political-military context (Lucullus, Pompey and Cicero), then within the political-religious context (including the ficus Ruminalis), and finally Cicero’s ideas of and engagement with Pompey’s triumph and theatre complex. I argue that Cicero’s arboreal attitude depended on his attitude to the notions and relationships the trees were made to symbolise, and how these related to his own notions of correct Roman elite behaviour.